(untitled) (Research, Society and Development, 2022)
The present study aimed to discuss the safe techniques for a laparoscopic cholecystectomy. Integrative literature review with data collection in the following databases: PubMed, UpToDate and Scielo. The descriptors were used: “Safe laparoscopic cholecystectomy”, “Anatomical references for videocholecystectomy”, “Laparoscopic cholecystectomy”. Totaling in a selection of 39 articles discussed. Currently, the laparoscopic approach is the gold standard for cholecystectomy, being considered a basic laparoscopic procedure, because the gallbladder is fixed to the liver and with this, the surgeon works in a single quadrant, avoiding large displacements in the abdominal cavity. However, for the technique to be developed in a safe way for both the surgeon and the patient, a rich anatomical knowledge is essential. Initially, a detailed abdominal inspection is necessary, aiming at the correct choice of the site of entry of the trochanters. After that, the surgeon should opt for the Critical View technique. After that, it is necessary to know some fixed anatomical landmarks to find the safe zone of dissection delineating the cystic duct and the cystic artery. Finally, it is important that a time limit is established for each step. Such a procedure, if followed correctly, is considered very safe, however, the risk of bile duct injury remains a significant concern, particularly in difficult laparoscopic cholecystectomy or with aberrant anatomy. Thus, the causes of biliary injuries are classified into two types: problems of incorrect identification of the anatomy and problems of technique.